image (136)

Substitution of A1, B2 from Eq. (120) into Eq. (136) yields

σxxA=μ[(ξ2+ηS22ηP2)2ξηSsinηSdsinηPy2ξηS(ξ2ηS2)sinηPdsinηSy]σyyA=μ[(ξ2ηS2)2ξηSsinηSdsinηPy+2ξηS(ξ2ηS2)sinηPd(sinηSy)]σxyA=iμ[2ξηP2ξηSsinηSdcosηPy+(ξ2ηS2)(ξ2ηS2)sinηPdcosηSy] (137)

image (137)

Upon expansion and rearrangement, Eq. (137) becomes

σxxA=2μξηS[(ξ2+ηS22ηP2)sinηSdsinηPy(ξ2ηS2)sinηPdsinηSy]σyyA=2μξηS(ξ2ηS2)(sinηSdsinηPysinηPdsinηSy)σxyA=iμ[4ξ2ηPηSsinηSdcosηPy+(ξ2ηS2)2sinηPdcosηSy] (138)

(138)

Showing explicitly the x,t dependency through the common factor ...

Get Structural Health Monitoring with Piezoelectric Wafer Active Sensors, 2nd Edition now with O’Reilly online learning.

O’Reilly members experience live online training, plus books, videos, and digital content from 200+ publishers.